Assessment of earthquake resistant techniques in the out-of-plane behaviour of stone masonry walls - Murano, Antonio (2019)
FE method is a useful and powerful tool widely applied to the structural analysis of masonry constructions. One of the main challenges related to the numerical simulations is the use of adequate constitutive materials models able to replicate, in an accurate way, the non-linear behaviour of masonry. Thus, the experimental characterization of the masonry can allow overcoming the uncertainties regarding the material mechanical properties. Macro-modelling is a very popular FE approach that approximates masonry as a homogeneous isotropic continuum, in order to obtain simpler and larger meshes, because the model does not have to describe the internal structure of masonry. Hence, macro-modelling provides a good balance between accuracy and efficiency. This work presents a methodology applied to the calibration of two numerical macro-models reproducing the OOP response of reduced scale (1:2) U-shaped stone masonry walls built with earthquake resistant techniques embedded at the corners (WALL 1 – steel ties and WALL 2 – timber lath beams), which were previously tested experimentally by using an airbag to simulate the seismic load. The outcomes, provided by this work, represent a useful contribution in order to assess the effectiveness of the macro-model approach for the analysis of masonry buildings.